(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
In this paper we analyze the Company History of Diaz Rubin brothers in Puebla between 1878 and 1914. Diaz Rubin family came from Asturias in order to settle down in Puebla in the last quarter of the twentieth century. First of all, we have to mention that their immigrant condition was a defining factor to start their commercial and industrial business because they continued a family tradition which was a very common pattem among the Spanish groups during Porfirio Diaz period. The article also analyzes the water and land hoarding made by Dfaz Rubin brothers in order to eam money to invest in their businesses. This paper highlights three main factors in the business activity: the buyout and modernization of the sugar mills in Izicar, the setting up of textile factories in Puebla and Atlixco and the establishment of grocery stores. Furthermore, this article studies other investments made on banking and railways.